(untitled) - Furuichi, Noritoshi (Tokyo, 2017)
The Happy Youth of a Desperate Country, a magnum opus by acclaimed sociologist Noritoshi Furuichi, has revoltionized the discourse on youth theory in Japan. Containing more than six hundred footnotes, this work offers a probing examination of the portrait of "young people" and serves as the definitive edition for anyone seeking to attain a wide-ranging grasp of Japan and its "young people," from a defining voice of their generation.
Keywords: Nhật Bản,Japan; Phong tục và đời sống xã hội,Social life and customs